2013
DOI: 10.12720/joig.1.1.39-42
|View full text |Cite
|
Sign up to set email alerts
|

A New No-Reference Image Quality Measure for Blurred Images in Spatial Domain

Abstract: Determination of quality of an image is a very challenging task and is very important for modern image processing applications. One of the most common distortions in images is blurring. For a human visual system excessive blurring in an image is not visually pleasing and creates difficulty in identifying objects. In this paper we propose a quality measure which is calculated in spatial domain to determine the quality of blurred images. 

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…These relations can be used to justify the computational advantage in considering (14) instead of (12) in the SIFT applications. As an example, for d = 4, the cases σ cascade < 8/3 and 8/3 ≤ σ cascade < √ 8 occur respectively two times per octave, giving a reduction in number of operations for 4 filters out of 5 (per octave).…”
Section: Proposed Method: Fast Eboxmentioning
confidence: 99%
See 1 more Smart Citation
“…These relations can be used to justify the computational advantage in considering (14) instead of (12) in the SIFT applications. As an example, for d = 4, the cases σ cascade < 8/3 and 8/3 ≤ σ cascade < √ 8 occur respectively two times per octave, giving a reduction in number of operations for 4 filters out of 5 (per octave).…”
Section: Proposed Method: Fast Eboxmentioning
confidence: 99%
“…Box filters introduce noise on edges, known in image processing as ringing artifacts. To quantify this, we used the Blur Measure (BM), defined in [14] as :…”
Section: Accuracy Of the Iterative Ebox Filteringmentioning
confidence: 99%
“…The pH sensors were obtained from six different batches. Since the preliminary studies demonstrated a strong agreement between the colour features of 3 to 5 consecutive images of the sensors, one image was captured from each sensor unless the image was blurry [ 4 ] due to ambient vibrations. The images had a size of 2048 by 1536 pixels.…”
Section: Methodsmentioning
confidence: 99%
“…The blur measurement method [4] mainly involves using Sobel operators to measure image edges, and the measurement results are compared with those obtained using the just noticeable blur (JNB) method. This method yields higher difference of mean opinion scores.…”
Section: Related Workmentioning
confidence: 99%
“…Image distortion-related studies, such as those on blur, the blocking effect, and sharpness, have produced favorable results [5,[12][13]. The blur measure (BM) method [4] is an algorithm based on the NR image quality assessment method, in which the Sobel algorithm is used to detect image edges. In the Sobel measurement method, one-dimensional analysis is first used to identify the pixel with the largest change in edge color, after which two-dimensional analysis is conducted.…”
Section: Introductionmentioning
confidence: 99%